Evaluasi Efektivitas Normalisasi dalam Mereduksi Banjir Sungai Sadia Menggunakan HEC-RAS - Hartawan, I Putu; Harlan, Dhemi; Mertawiasa, I Nyoman Yogi; Irwansyah, Deddy; Wicaksono, Arief Yudho (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2026)
Bima City is an area with a relatively high risk of flooding and experiences flooding almost every year. One of the main causes of flooding is the limited capacity of the Sadia River to accommodate the flow from the upper reaches of the Sadia Watershed (DAS), especially during periods of high-intensity and long-duration rainfall. As a flood control measure, the BBWS NT I have carried out structural measures in the form of normalizing the Sadia River along a length of ±4.5 km. This study aims to assess the performance of river normalization in reducing the area and depth of flooding around the Sadia River. The novelty of this study lies in the use of long-term satellite rainfall data for flood analysis. The study was conducted on a ±4.5 km segment of the Sadia River. The hydrological analysis began with a study of the watershed characteristics to determine the input flood discharge using HEC-HMS. Rainfall data were obtained from the Global Precipitation Measurement (GPM) satellite for the period 2001–2024, which was calibrated and tested for correlation with rainfall data from the Rainfall Observation Station (PCH Kumbe). The 25-year return period flood discharge (Q25) was determined using the Nakayasu Synthetic Unit Hydrograph method, calibrated using the bankfull discharge (Q2). Hydraulic analysis was performed using HEC-RAS 1D to obtain water surface profiles and HEC-RAS 2D to map flood inundation patterns, calibrated against the 2016 flood event. Simulations were conducted for two conditions: existing conditions, and post-river normalization conditions. The analysis results show that under existing conditions, the Sadia River is unable to accommodate a Q25 flood discharge of 167 m³/sec, with a flood area of 89.87 ha and a depth of 0.1–4.0 m.After normalization, the flood area can be reduced by 40.74%.